(untitled) (Archive of Conferences, 2021)
The article describes the work being done to introduce modern mechanisms for resolving disputes in the field of labor law. Also, other (alternative) methods of resolving labor disputes have been analyzed on the basis of research conducted by the International Labor Organization’s Research Center and the experience of developed countries.